Translation Strategies In The Translation Of Idioms In Shakespeare’s Romeo And Juliet - ABDELAAL, N.; ALAZZAWIE, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Translating idioms is challenging for translators due to the cultural differences between a source language and a target language. In this regard, this research aimed to identify the translation strategies adopted by Anani in the translation of Romeo and Juliet, and the extent of the source text (ST) meaning of the idioms was conveyed in the target text (TT). A qualitative analysis was conducted to identify such translation strategies and determine the extent of ST meaning of such idioms was conveyed. Baker’s translation strategies were used as a theoretical framework of the research. RESUMEN Traducir modismos es un desafío para los traductores debido a las diferencias culturales entre un idioma de origen y un idioma de destino. En este sentido, esta investigación tuvo como objetivo identificar las estrategias de traducción adoptadas por Anani en la traducción de Romeo y Julieta, y la extensión del significado del texto fuente (ST) de los modismos que se transmitió en el texto objetivo (TT). Se realizó un análisis cualitativo para identificar tales estrategias de traducción y determinar el grado en que se transmitió el significado ST de tales expresiones idiomáticas. Las estrategias de traducción de Baker se utilizaron como marco teórico de la investigación.